Prakriti (Ayurvedic concept of constitution) and variations in platelet aggregation - Bhalerao Supriya; Deshpande Tejashree; Thatte Urmila (BMC, 2012)
Abstract Background Ayurveda, the Indian traditional system of medicine describes a unique concept "prakriti", genetically determined, categorising the population into several subgroups based on phenotypic characters like appearance, temperament and habits. The concept is claimed to be useful in predicting an individual's susceptibility to a particular disease, prognosis of that illness and selection of therapy. The present study was carried out to study if the platelet aggregatory response and its inhibition by aspirin varied in the different prakriti subtypes. Methods After obtaining Institutional Ethics Committee permission, normal healthy individuals of either sex between the age group 18 to 30 years were recruited in the study. Their prakriti evaluation was done using a standardized validated questionnaire (TNMC Prakriti 2004). Their Platelet Rich Plasma was incubated with either aspirin [2.5micro-mole (μM) and 5μM] or distilled water as control for three minutes after which the aggregatory response to 5μM Adenosine Diphosphate (ADP) was measured over a period of 7 minutes. Results We observed that in the study population of normal healthy participants (n= 137), ADP-induced maximal platelet aggregation (MPA) was highest among the Vata-pitta prakriti individuals [Median (range), 83.33% (52.33-96)] as compared to the other prakriti types and these individuals responded better to lower dose of aspirin compared to other prakriti types. Conclusions Our results suggest that identifying the prakriti may help in individualising therapy or predicting proneness to a disease.